Compulsory vehicle inspection policy in solving issues arising: a comparative study / Muhammad Nizam Sulaiman, Muhammad Akif Ruslan and Muhammad Faris Rosli - Sulaiman, Muhammad Nizam; Ruslan, Muhammad Akif; Rosli, Muhammad Faris (2011)
Vehicle is commonly used for humans to go from a place to another faster or to go to another place by bringing a lot of things or heavy things. Hence, Vehicle is an important thing for human being to undergo their daily life activities such as going to work, going to buy food to eat and etc. Due to this importance, vehicles need to be in good condition for them to be used without any problems so that the owners would be able to carry out their activities without interruption. One of The ways to curb such unwanted situation is to have vehicles inspection. However, the requirements to have vehicle inspection in Malaysia are not strict as in the United Kingdom. Due to this, many problems which are vehicle related such as accidents, fraud, vehicle gas emission occurred. There are many accidents occurred in Malaysia, especially during the festive season. Most of the reasons identified as cause of accidents are due to car failures such as unsatisfactory tire condition, car losing control due to the condition of absorbers and etc. Furthermore, there are many second-hand car- owners who are being cheated where the car seller sold defective car or not of merchantable quality cars to the buyers. It leaves injustice on part of the buyer because the buyer then has to pay extra cost to fix the car or in worst case scenario may, put the buyer's life at risk. The buyer could get into accident due to car failure. Over the last decade, the number of cars that are driven in Malaysia has doubled.1 . A high number of vehicles in urban areas are reported as the main contributor of the air pollution although it is understandable that the air pollution is inevitable, however, it is possible to reduce the emission of it.